PERAN DAN STRATEGI GURU AGAMA HINDU DALAM MEMBANGUN KARAKTER JUJUR DAN DISIPLIN - Putu Diapurnaman; Agung Adi; Dewi Sinta (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
Honest and disciplined character is the foundation of values in forming individuals who have superior and responsible qualities. To build these two characters, teachers have certain roles and strategies. This research aims to explain the various roles and strategies of Hindu religious teachers at SMAN 4 Palangka Raya City in building honest and disciplined character. Role theory and gestalt cognitive theory are used as the basis for analysis. Research method with a qualitative approach. Meanwhile, data collection was carried out through observation techniques, in-depth interviews, and document studies. On the other hand, data analysis is carried out through an interactive model, which includes the entire process of data collection, sorting, presentation, and conclusions. Based on the analysis, the role of Hindu religious teachers in building honest and disciplined character includes the role of a catalyst; namely, the teacher acts more as a role model by emphasizing speech or words that are always based on the heart or conscience. Another role is as a guide, through the experiences they have and referring to Hindu teaching sources. The next role is as a motivator, encouraging students to comply with class and school rules by providing rewards or sanctions. Meanwhile, the strategy used by Hindu religious teachers is to integrate the concepts of honesty and discipline into Hindu religious lessons. The next strategy is to always try to create a conducive environment, namely by writing wise sentences on the walls of classrooms, libraries, and trash cans with the aim of making students aware of the importance of honest and disciplined character. The final strategy is to collaborate with parents or students' families on an ongoing basis